Amino Acid Supplementation Improves the Production of Extracellular Peptidases by Aspergillus Section Flavi and their Ionic Immobilization - Gonsales Rosa-Garzon, Nathalia; Rodrigues de Siqueira, Ana Claudia; Naomi Hirano, Viviane; Rodrigues, Andre [UNESP]; Costa Pessela, Benevides; Cabral, Hamilton (Inst Tecnologia Parana, 2020)
Bioprocess studies have been highlighted due to the importance of physiological processes and industrial applications of enzymes. The potential of peptidase production from Aspergillus section Flavi using different amino acids as a supplemental nitrogen source was investigated. A production profile revealed that amino acids had positive effects on peptidase production when compared to the control without amino acids. Optimal production (100 U/mL) was obtained with Arginine amino acid in 96 h of fermentation. Extracellular peptidase from Aspergillus section Flavi was identified in submerged bioprocesses by in situ activity. Biochemical studies revealed that the maximum activities of the enzyme extract were obtained at pH 6.5 and a temperature of 55 degrees C. The inhibition by EDTA and PMSF suggests the presence of more than one peptidase while the Ni2+ and Cu2+ had a negative influence on the enzyme activity. When the crude extract was reversibly immobilized on ionic supports, DEAE-Agarose and MANAE-Agarose the derivative showed different profiles of thermal and pH stabilities. Hence, this study revealed the basic properties and biochemical characteristics that allowed the production improvement of this class of enzyme. Moreover, with known properties stabilization and immobilization process is required to further explore its biotechnological capacities.
Keywords: filamentous fungi; immobilization; MANAE-agarose; submerged bioprocess; protease